(untitled) (Jurnal Pengajaran Matematika dan Ilmu Pengetahuan Alam, 2013)
This research is about characteristic of mechanics teaching for increasing students of physics teacher candidates representation ability on verbal, mathematical, picture, and graphic. Research problem is about how the characteristic of mechanics teaching materials can help students of physics teacher candidates increasing their representation ability on verbal, mathematical, picture, and graphic. This research problem translated into two questions. First, how is the mechanical teaching materials consists of examples of mechanics principle application in physics event pictures. Second, how is the pattern of writing mechanical teaching materials for students of physics teacher candidates. This research is the development of mechanics teaching materials, using mix methods investigation model, those are: collecting qualitative data, building mechanical teaching, material draft so it will ready for validating. Research subject on this mechanical teaching materials are hopely able to increase students’ representation ability on verbal, mathematcal, picture, and graphic. The respondent of this research are students’ physics teacher candidates that taking basic physic subject in faculty of teacher training and education, Jember university. The technic of collecting data are observation, questionnaire, test and documentation. The data were qualitatively described. The research result shows that mechanical teaching materials’ consist of examples of mechanics principle application in physics event pictures and having written pattern that are title sequence chapters, title sub chapters, material description, example of test, test of ability and bibliography. Penelitian ini adalah tentang karakteristik pengajaran mekanik untuk meningkatkan kemampuan representasi mahasiswa calon guru fisika pada verbal, matematika, gambar, dan grafis. Masalah penelitian adalah bagaimana karakteristik bahan ajar mekanik dapat membantu mahasiswa calon guru fisika dalam meningkatkan kemampuan representasi mereka pada verbal, matematika, gambar, dan grafis. Masalah penelitian ini diterjemahkan ke dalam dua pertanyaan. Pertama, bagaimana bahan ajar mekanik terdiri dari contoh aplikasi prinsip mekanika dalam gambar peristiwa fisika? Kedua, bagaimana pola penulisan bahan ajar mekanik bagi mahasiswa calon guru fisika? Penelitian ini merupakan pengembangan bahan ajar mekanika, menggunakan metode campuran model investigasi, yaitu: pengumpulan data kualitatif, membangun pengajaran mekanik, rancangan materi sehingga akan siap untuk divalidasi. Subjek penelitian diharapkan mampu meningkatkan kemampuan representasi pada verbal, matematika, gambar, dan grafis. Responden penelitian ini adalah mahasiswa fisika calon guru yang mengambil subjek fisika dasar fakultas keguruan dan pendidikan, Universitas Jember. Adapun teknik pengumpulan data adalah: observasi, angket, tes dan dokumentasi. Data dijabarkan secara kualitatif. Hasil penelitian menunjukkan bahwa bahan ajar mekanik terdiri dari contoh aplikasi prinsip mekanika dalam gambar acara fisika dan memiliki pola urutan bab, judul sub bab, deskripsi materi, contoh, uji kemampuan dan bibliografi.